Effective Width of Composite L-Beams in Buildings - Brosnan, David P.; Uang, Chia-Ming (Engineering Journal, 1995)
The latest AISC design specifications permit the use of wider effective widths for steel-concrete composite exterior beams (or L-beams) than previous editions. This sometimes results in more flexible beams which quite often support deflection-sensitive nonstructural components. An analytical study of composite L-beams was conducted within a practical range of span and spacing for buildings. Both the conventional stress-based and rational stiffness-based definitions of effective width were considered. Effective widths were computed from the results of finite element analysis of three dimensional models permitting longitudinal slip between the concrete slab and the steel beam. It was concluded that the AISC effective width criteria for L-beams tends in an unconservative direction; a stiffness-based formula dependent on the spacing/span ratio is proposed.